16 - Impact of HIV/Aids on the Labour Force: Exploring Vulnerabilities Abstract - Jocelyn R. Vass (CODESRIA Bulletin, 2003)
This paper explores the impact of HIV/Aids on vulnerability in the labour market, and in the labour force specifically. Research to date has concentrated on the social-behavioural and macro-economic impact of HIV/Aids on the development agenda of the hardest-hit countries, especially in sub-Saharan Africa. Understandably, most of the analysis is geared at establishing the scale and nature of the pandemic, as well as emphasising the human tragedy that is unfolding. Most labour market analysis derives from macro-economic simulation studies as well as the few firm and sector level studies in the public domain. The focus is largely on risk assessment in relation to mortality and morbidity costs faced by governments, businesses and households. However, what is often neglected is the risk faced by the labour force in terms of increased vulnerability, the extent to which it will have to carry the Aids burden, and how the balance of power between business and labour may be shifted in terms of collective bargaining. In this paper, I argue that there is an interdependent relationship between HIV/Aids and social and labour market inequalities. HIV/Aids disproportionately affects the most vulnerable and marginalised in society and in the labour force. It therefore deepens unequal relations of power, both in the structure and organisation of production and in the labour market as a whole. This paper takes South Africa as a case study and examines the challenges it faces in redressing inherited social and economic inequalities in the context of the HIV/Aids epidemic..